One Dy I Kud Not Red a Book Bot Naw I Can: One English Learner's Progress. (6th May 2013) - Amendum, Steve; Amendum, Emily; Almond, Pamela
Abstract: This article describes a year‐long reading intervention with a first‐grade English‐learner who began the year as a non‐reader. Systematic instruction from a literacy specialist and her classroom teacher included familiar re‐reading, word study, and teacher‐guided reading with carefully matched texts, within the context of English language and vocabulary development. Intervention instruction facilitated this young English learner's grade‐level achievement by the end of the school year. Intervention strategies, intensity, and the student's progress are described.